Formación en valores y su incidencia en el desarrollo comportamental de los estudiantes de 6º año de básica en la Unidad Educativa N.º 1 Oriente Ecuatoriano del cantón El Empalme, Provincia del Guayas periodo lectivo 2019 - 2020 - Pacheco López, José Roberto (2020)
The lack of values that students currently have is one of the greatest difficulties suffered by some students of Educational Unit N ° -1 "East Ecuadorian" and that are evident within this great institution of education, originating behavioral problems without Measure the consequences of these actions. The ignorance of the importance of values is worrisome and should prevail in each of the homes and also within the classroom of educational institutions, it is necessary to teach how compelling are the values and how their shortcomings impact on the behavioral and educational development of the students of this prestigious Educational Unit. This project is going to be carried out with an internal campaign based on workshops with themes related to values in order to enhance and stimulate the affective - intellectual capacities, so that they are capable of creating pleasant environments to carry out an adequate development of meaningful learning